A New Synthetic Pathway for the Bioproduction of Glycolic Acid From Lignocellulosic Sugars Aimed at Maximal Carbon Conservation - Lachaux, Cléa; Frazao, Cláudio J. R.; Krauβer, Franziska; Morin, Nicolas; Walther, Thomas; François, Jean Marie (Frontiers in Bioengineering and Biotechnology, 2019)
Glycolic acid is a two-carbon -hydroxy acid with many applications in industrial sectors including packaging, fine chemistry, cosmetics and pharmaceutics. Currently, glycolic acid is chemically manufactured from fossil resources. This chemical mode of production is raising some concerns regarding its use in health for personal care. Microbial production of GA stands as a remarkable challenge to meet these concerns, while responding to the increasing demand to produce bio-sourced products from renewable carbon resources. We here report on the design and expression of a novel non-natural pathway of glycolic acid in E. coli. The originality of this new pathway, termed ‘glycoptimus’ relies on two pillars. On the one hand, it requires the overexpression of three naturally occurring E. coli genes, namely kdsD encoding a D-arabinose-5-P isomerase, fsaA encoding a class 1 aldolase that cleaves D-arabinose-5-P into glyceraldehyde-3-P and glycolaldehyde, and aldA coding for an aldehyde dehydrogenase that oxidizes glycoladehyde in glycolate. These three genes constitute the ‘glycoptimus module’. On the other hand, the expression of these genes together with a reshaping of the central carbon metabolism should enable a production of glycolic acid from pentose and hexose at a molar ratio of 2.5 and 3, respectively, which corresponds to 50% increase as compared to the existing pathways. We demonstrated the ‘in vivo’ potentiality of this pathway using an E. coli strain, which constitutively expressed the glycoptimus module and whose carbon flow in glycolysis was blocked at the level of glyceraldehyde-3-P dehydrogenase reaction step. This engineered strain was cultivated on a permissive medium containing malate and D-glucose. Upon exhaustion of malate, addition of either D-glucose, D-xylose or L-arabinose led to the production of glycolic acid reaching about 30 % of the maximum molar yield expected. Further improvements at the level of enzymes, strains and bioprocess engineering are awaited to increase yield and titer, rendering the microbial production of glycolic acid affordable for a cost-effective industrial process.